THE RELATIONSHIP BETWEEN THE EUROPEAN PUBLIC PROSECUTOR’S OFFICE AND THE OTHER JURISDICTIONAL BODIES AT THE EU LEVE - Miron-Paul, CHICHIȘAN (International Journal of Legal and Social Order, 2022)
Judicial cooperation in criminal matters represents one of the novelties of criminal law in the European Union. The purpose of this work is to highlight the role that the EU judicial institutions have in the fight against the phenomenon of white collar crime. Knowing that only one institution is working very hard in the fight against a phenomenon that has gained momentum in recent years, financial fraud against the EU, we must refer to their collaboration. Thus, we will analyze the collaboration of the European Prosecutor's Office with other prestigious institutions such as OLAF or EUROJUST, as well as with the specialized structures within the participating states, but also the trend of collaboration with third countries.